PENENTUAN ELEVASI PERMUKAAN AIR BERDASARKAN DATA SERIES TINGGI TEKANAN AIR - Rusdin, Andi (MEKTEK, 2011)
Series data of sea surface elevation is required to determine the parameters of tidal and wave parameters.The series data on sea water surface is irregular waves which are a superposition of several regular waves.Therefore, water surface parameters are usually based on statistical parameters. Statistical parameter ofwater surface can be obtained by performing frequency analysis on data series of water surface elevationobtained by field measurements. The water surface elevation can be also determined by converting dataseries of water pressure obtained by pressure sensors. In this paper, the water surface elevation that has asmall oscillation period is calculated based on two methods i.e. method of linear wave theory and methodTransform Fast Fourier (FFT). The water surface elevation that is calculated by using linear wave theorymethod is converted directly from data series of water pressure that consists of hydrostatic pressure anddynamic pressure. FFT method has two steps to convert water pressure to become water surface elevation.First of all data series of water pressure is fragmented into several regular waves based on their frequencies.Secondly, In order to reduce errors, water level fluctuations with high frequencies are removed from the databased on the maximum frequency that can be recorded by the measuring instrument. The maximumfrequency is determined by applying a deep-sea conditions and the depth position of the pressure sensor.Data used in the calculation is data from LIP11D experiments conducted at Delft LIP11D Hydraulic. Threedata sets of water pressure were used to compare the water surface elevation of direct measurements withtwo water pressure conversion results using linear wave theory and the FFT method. Results of analysisshow that the water surface elevation obtained by the FFT method gives good results when compared withthe results of direct measurements